Adaptation of a financial toxicity intervention for scale-up to diverse contexts: Core functions of Lessening the Impact of Financial Toxicity (LIFT). Issue 28 (1st October 2022) - Birken, Sarah A; Wheeler, Stephanie B.; Wagi, Cheyenne; Manning, Michelle L.; Strom, Carla; Bell, Ronny A.; Gellin, Mindy; Padilla, Neda; Rogers, Cindy; Rodriguez-O'Donnell, Julia; Rosenstein, Donald L.
Abstract : 345 Background: Rural and non-English speaking populations experience a disproportionate burden of financial toxicity and access to services for their cancer care. Lessening the Impact of Financial Toxicity (LIFT) is an intervention designed to address financial toxicity (FT) through financial navigation (FN). FN identifies patients at risk for FT, assesses eligibility for financial support, clarifies costs, and develops strategies to cope with costs. LIFT was successful in reducing financial toxicity in preliminary studies among English-speaking patients with high levels of FT in a single large academic cancer center. To benefit diverse patients with FT in cancer programs across the US, there is a need to adapt LIFT. Adapting LIFT requires distinguishing between its core functions— the components of LIFT key to its effectiveness and implementation, and its forms— the activities that comprise LIFT, facilitate its implementation, and may be adapted to accommodate new populations and contexts. We completed the first stage of adaptation, identifying LIFT core functions. Methods: We conducted interviews with individuals responsible for LIFT's design and implementation. Interview questions were based on Kirk's methods for identifying core functions and were recorded and transcribed verbatim. Using a codebook based on the Model for Adaptation Design and Impact, we coded interview transcripts and identified themes related to how LIFT engaged cancer program staff in FN (implementation core functions) and decreased FT (intervention core functions). Results: Eight interview participants filled various roles in designing and implementing LIFT (e.g., P.I.s; FNs). LIFT intervention core functions include a systematic way of cataloging knowledge, resources, and tracking patient information; using patient-specific needs to guide access to resources; ongoing, dynamic assistance and strong one-on-one relationships between navigators and patients; and removing common barriers to accessing resources. Conclusions: We identified core functions key to LIFT's effectiveness and implementation. Next steps include identifying systematic differences between LIFT's original context and population and new ones. Successfully adapting LIFT has the potential to extend its benefits to diverse patients in cancer programs throughout the US, such as Spanish-speaking patients served by rural community cancer programs.